Asexual Erotics Intimate Readings of Compulsory Sexuality - Przybylo, Ela (The Ohio State University Press, 2019)
Asexual Erotics: Intimate Readings of Compulsory Sexuality attends to the silence around asexuality in queer, feminist, and lesbian thinking from the late 1960s to the present. Drawing on the knowledge generated by asexual community, activism, and scholarship, Ela Przybylo gives us the first queer and feminist monograph on asexuality.